Visualizing fractions with Geogebra - Tambi, N.; Leong, K.E. (2013)
The purpose of this study is to investigate the visualization of fractions using GeoGebra. Some studies had shown that students have poor conceptualization in visualizing fractions. Using GeoGebra enhances the understanding of fractions. GeoGebra provides a platform to construct fractions using rectangles. Students are able to understand the meaning of numerators over denominators symbols. Quasi experiment is used to compare the achievement of two groups of Year Four primary school students. Results indicate that there is a significant difference between the two groups. The findings are useful to propose an alternative way of learning fractions as well as assisting students in visualizing fractions using GeoGebra.